Influences of the quasi-two-day wave on plasma bubble behavior over south America - Bossert, Katrina; Kumari, Komal; Inchin, Pavel; Norrell, Jessica; Eckermann, Stephen; Pautet, Pierre-Dominique; Martinis, Carlos; Kjellstrand, Carl Bjorn; Phillips, Sophie; Snively, Jonathan; Zhao, Yucheng; Zettergren, Matthew (Frontiers in Astronomy and Space Sciences, 2024)
Equatorial Plasma Bubbles (EPBs) are a region of depleted ionospheric densities. EPBs are known to fluctuate both seasonally and day to day, and have been linked to changes in solar activity, geomagnetic activity, and seeding resulting from dynamics occurring at lower altitudes. Here, EPB activity is investigated over a 15-day period with overlapping coincident ground-based 630 nm oxygen airglow measurements, near-infrared hydroxyl mesospheric temperature mapper (MTM) measurements, and Rate Of change of Total Electron Content Index (ROTI) values. The data are compared with the Navy Global Environmental Model (NAVGEM) reanalysis over the same time period. It is found that several days with strong EPB activity coincided with the positive/northward meridional wind phase of the quasi-two-day wave (QTDW) in the mesosphere. These initial observations indicate correlations of the QTDW phase and the occurrence rates of EPBs, and suggest a need for further investigations to assess potential causal relationships that may affect the variability and prevalence of EPBs.